RANCANG BANGUN SISTEM INVENTORI KONTROL DALAM MENUNJANG PELAYAN UNTUK MENINGKATKAN KEPUASAN PELANGGAN - Deden Roni Nurjaman; Fernando Siboro; Angga Hardiyanto Pranata (UNIVERSITAS RAHARJA, 2019)
Companies that are engaged in general trading, suppliers and distributors for the procurement of goods or equipment and services to assist the operations and management of companies, especially improving company services in the field of drinking water are still using manual systems, where data is reported in written form, making it difficult , ineffective and efficient in inputting data and searching for goods. Therefore, this study proposes making a control inventory system to create a faster, more precise and accurate system. The analysis and modeling systems for programs use unified modeling language (UML) as a tool to help in object-oriented programming languages which are then implemented with the php programming language and use MySQL as a database. From this study, an inventory system can be produced that can monitor stock of goods in the warehouse properly, effectively and efficiently so that it can support services and improve customer satisfaction.